The Relationship of the Quintuple Helix in Strengthening the Pancasila Character in the Millennial Generation for the Indonesian Nation - Lailatul Fitria, Nurul Jannah (Universitas Muhammadiyah Surakarta, 2023)
Indonesian worldview incorporates Godhead, humanity, unity, democracy, and social justice from communal life. Youth are alienated from Pancasila. They prefer modern, creative, and innovative social values. Exploring this to reinforce Pancasila ideals for youth is important. This study examines five interconnected helixes to reinforce Pancasila. The five helixes are education, economy, society, politics, and environment. This research used descriptive qualitative methods. Research data came from a literature review. Results suggest that the Quintuple Helix strengthens Pancasila for millennials. The quintuple helix interaction in Indonesia describes how academics, government, economic actors, society, and the natural environment promote innovation. Technically, not all helixes produce innovation because their roles and portions vary.